Test protocol for in-situ bicycle wheel dynamic comfort comparison - Lepine, J.; Champoux, Y.; Drouet, J.-M. (Procedia Engineering, 2016)
Bicycle comfort is very important especially for enthusiastic road cyclists who can spend several hours astride their bicycle in a single ride. Being an abstract concept, several researchers proposed to assess bicycle comfort by measuring the level of vibration transmitted to the cyclist. This can be measured in a controlled laboratory environment but it requires cumbersome and expensive road excitation simulation setup. In-situ measurements are an alternative solution but the experiment repeatability is not as good as in the laboratory because many experimental factors are difficult to control while riding a bicycle on the road (e.g. cyclist's posture on the bicycle). This paper presents a test protocol to evaluate bicycle comfort with minimal uncertainty inherent of the in-situ experiment. Three main elements are used to enhance measurement repeatability and therefore increase the differentiating capability of the protocol: the measurand selection, the bicycle propulsion and the design of experiments. The power absorbed by the cyclist is used to quantify the level of vibration transmitted to the cyclist because it is far less sensitive to variation of cyclists` posture than to the other measurands used to assess comfort such as acceleration. The bicycle is propelled from an external source which increases precision of the bicycle speed control during the experiment and eliminates measurement noise coming from the bicycle drivetrain. The experiment is specifically designed in term of test runs` duration and replication to improve its repeatability. The protocol is presented in this paper as a case study of bicycle wheel comfort comparison and can be extended to any components or a complete bicycle comfort comparison. The same case study has been performed with different test methods in the laboratory which are used to assess and validate the accuracy of the presented in-situ protocol.